2011
DOI: 10.1021/ac103070t
|View full text |Cite
|
Sign up to set email alerts
|

IncreasedIn VivoGlucose Recovery via Nitric Oxide Release

Abstract: The in vivo glucose recovery of subcutaneously implanted nitric oxide (NO)-releasing microdialysis probes was evaluated in a rat model using saturated NO solutions to steadily release NO. Such methodology resulted in a constant NO flux of 162 pmol cm -2 s -1 from the probe membrane over 8 h of perfusion daily. The in vivo effects of enhanced localized NO were evaluated by monitoring glucose recovery over a 14 d period, with histological analysis thereafter. A difference in glucose recovery was observed startin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(44 citation statements)
references
References 45 publications
1
43
0
Order By: Relevance
“…After 1 week, there was a cellular layer near the tissue-hydrogel interface composed mainly of macrophages and fibroblasts which is defined as the MF layer [40]. Cell density was calculated by counting cell nuclei (black in Masson’s Trichrome staining) in the MF layer in three 50 μm × 100 μm area on each slides [41]. Collagen density (blue in Masson’s Trichrome staining) was quantified in three 50 μm × 100 μm fields adjacent to the MF layer using a previously developed MATLAB (MathWorks, Natick, MA) program [42].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…After 1 week, there was a cellular layer near the tissue-hydrogel interface composed mainly of macrophages and fibroblasts which is defined as the MF layer [40]. Cell density was calculated by counting cell nuclei (black in Masson’s Trichrome staining) in the MF layer in three 50 μm × 100 μm area on each slides [41]. Collagen density (blue in Masson’s Trichrome staining) was quantified in three 50 μm × 100 μm fields adjacent to the MF layer using a previously developed MATLAB (MathWorks, Natick, MA) program [42].…”
Section: Methodsmentioning
confidence: 99%
“…Collagen density (blue in Masson’s Trichrome staining) was quantified in three 50 μm × 100 μm fields adjacent to the MF layer using a previously developed MATLAB (MathWorks, Natick, MA) program [42]. 4-week samples were quantified by measuring the fibrous capsule thickness, as well as cell and collagen density located in the fibrous capsule [41]. To identify the cell types surrounding the implanted hydrogels, both 1- and 4-week sections were further stained by immunofluorescent staining markers for rat fibroblasts (green, Anti-S100A4 antibody and goat antirabbit IgG H&L (Alexa Fluor® 488)) and macrophages (red, anti-CD68 antibody and goat antirabbit IgG H&L (Alexa Fluor ® 647)) [36].…”
Section: Methodsmentioning
confidence: 99%
“…Several CGM combination device strategies have sought to use device-based drug delivery from the sensor to "condition" the implant site pharmacologically and enhance the local CGM sensor-tissue interface ( Nichols et al, 2011;Ward and Troupe, 1999;Ward et al, 2004). Tissue mast cells have been shown to be important in eliciting the host FBR around CGM sensors in vivo during the acute inflammatory response stage, affecting their tissue site performance (Klueh et al, 2010;Tang et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…CGM surface coatings containing bioactive nitric oxide (Hetrick et al, 2007;Nablo et al, 2005;Nichols et al, 2011), dexamethasone (Bhardwaj et al, 2007;Hickey et al 2002a;Ju et al, 2010), and vascular endothelial growth factor (VEGF) (Golub et al, 2010;Klueh et al, 2013;Sung et al, 2009) all attempt to limit sensor fouling while exploiting a local pharmacological strategy to attenuate the intensity of the acute host inflammatory reaction. Each locally released drug and associated coating matrix approach has formulation, loading, and stability issues, different dosing requirements for given drug pharmacologies, and distinct tissue targets.…”
Section: Introductionmentioning
confidence: 99%
“…75 In subsequent work, Gifford releasing glucose sensor was characterized by a reduced run-in time (i.e., time required to stabilize sensor response after implantation). 71 While sensor success with only initial NO release was accomplished, Nichols and colleagues 90 showed that NO-releasing microdialysis probes further enhanced in vivo glucose recovery compared with controls over longer periods (up to 14 days). As shown in Figure 3, probes with daily NO fluxes of 162 pmol cm -2 s -1 over an 8 h perfusion period were characterized by constant glucose recovery over 14 days, reduced capsule thickness, and lessened inflammatory cell density at the probe surface.…”
Section: Active Releasementioning
confidence: 99%